Analysis of characteristic heat pipe as an efficient cooling heat transfer device - Alfan, Norman Hafizi (2013)
A heat pipe is a simple heat transfer device that can transport large quantities of heat with a very small difference in temperature between the hot ends to the other end. In this case study, the concept of the condensation process of heat pipe is applied in order to perform dehumidification process to remove extra moisture inside the air. The objective of this study is to compare the efficiency between the primary heat pipe in evacuated condition and the secondary heat pipe with water as the working fluid in order to perform the dehumidification process. The heat pipe device had been divided into 2 samples of specimens. First specimen of heat pipe using air whiles the other one used water as the working fluid. These two pipes were made without the wick but dealing with inclination of angle to see the performance of the heat pipe. These two heat pipes were built without the wick but dealing with inclination of angle to see the performance of the heat pipe. Both pipes were built by the total length of 400mm length and 8mm diameter using copper as the pipe material. Gravity pumping was used with the inclination angle to pump back the working fluid back to the evaporator section. The heat pipe was positioned at different angles of 0°, 30°, 60° and 90° with the horizontal. To achieve the objective of this study, both pipes were studied experimental and simulation to find the most efficiency between the primary heat pipe and the secondary heat pipe. The important parameter involves in the case study are the Merit Number, M and Heat Transfer Coefficient. After performing the experiments and simulation, the objective of this case study is achieved, which showed the secondary heat pipe is more efficient as a cooling heat transfer device.